Eveline Aelen, Wim Baeck, Siegfried Fonteyn, Colette Van Gompel, Stefan Zeyen : De Markten te 1000 Brussel Van 12 Juni tot en met 29 Juni 1992. - Delafortrie, Lieven; van Gestel, Fik; De Markten, Brussel (Brussel : Lieven Delafortrie, 1992)
Aelen, Eveline ; Baeck, Wim ; Fonteyn, Siegfried ; Van Gompel, Colette ; Zeyen, Stefan
De Markten, Brussel, van 12 juni tot en met 29 juni 1992
kunstcatalogus